Reflections on working in public-figure threat management. (October 2019) - Wilson, Simon; Farnham, Frank; Taylor, Alice; Taylor, Richard
The Fixated Threat Assessment Centre (FTAC) manages the risk posed to public figures by fixated individuals by paying attention to their correspondence and approaches and liaising with the mental health and criminal justice agencies responsible for their management. This paper offers a narrative reflection on the clinical experience of this unusual work. The clinical population is significantly different from that seen in mainstream mental health services, with a preponderance of delusional disorders and paraphrenias. The interface with mental health and criminal justice systems around the UK and internationally also offers a unique perspective on the functioning and malfunctioning of these services, and we attempt to describe and make sense of these experiences.